American English Today : The uses of language - Guth, Hans Paul (New York : Webster Division/McGraw-Hill, 1975)
An eleventh grade text offering instruction in the area of composition, word study, grammar, usage, mechanics, and speech.
Includes index.
Keywords: English language -- Usage -- Problems, exercises, etc; English language -- Composition and exercises; English language -- Usage